Acetylcysteine and budesonide for the treatment of refractory Mycoplasma pneumoniae pneumonia in children: a clinical observation - Yanli Wang; Kai Liu; Chuangui Chen; Chengyun Zhang (BMC, 2023)
Abstract Background To examine the clinical impact of bronchoscope alveolar lavage (BAL) combination with budesonide, ambroxol + budesonide, or acetylcysteine + budesonide in the treatment of refractory Mycoplasma pneumoniae pneumonia (RMPP). Methods Eighty-two RMPP patients admitted to Pediatrics at The First People's Hospital of Zhengzhou were retrospectively evaluated between August 2016 and August 2019. All patients were administered BAL in addition to intravenous Azithromycin, expectoration, and nebulizer inhalation. The medications added to the BLA separated the patients into the Budesonide group, Ambroxol + budesonide group, and acetylcysteine + budesonide group. Analyzed were the variations in laboratory examination indices, improvement in lung imaging, overall effective rate, and adverse responses in the three groups. Results The laboratory test indices of patients in all three groups improved significantly relative to pre-treatment levels, and the results were statistically significant. After therapy, there were no significant differences between the three groups in terms of white blood cell (WBC), C-reactive protein (CRP), or erythrocyte sedimentation rate (ESR). Serum lactate dehydrogenase (LDH) and serum ferritin (SF) varied significantly across the three groups (P < 0.05). In the acetylcysteine + budesonide group, the absorption rate of lung imaging lesions and clinical efficacy were superior to those of the other two groups. There were no significant differences between the three groups in the occurrence of adverse events (P > 0.05). Conclusions BLA-coupled acetylcysteine + budesonide was superior to the other two groups in enhancing the effectiveness of RMPP in children, which might increase lung opacity absorption and minimize lung inflammation.